Hydrograph fore - cas ting using the SWAT model (Soil and Water As sessment Tool) on the example of the Desna basin - Osypov, V.V.; Speka, O.S.; Osadchyi, V.I.; Osadcha, N.M.; Bonchkovskyi, A.S. (Reports of the National Academy of Sciences of Ukraine, 2020)
We evaluated the SWAT model (Soil and Water Assessment Tool) to predict the water runoff in the Desna river basin in 2020. This year was characterized by the abnormally low spring flood. The performance criteria of the calibration/validation for the previous period (2008-2019) were high (R2 = 0.85, NS = 0.85, PBIAS = —0.8 %) that allowed the use of SWAT for the operational forecasting. We computed the water runoff values for 116 subbasins of the Desna watersheds by 12 weather scenarios replicated the observations of the previous years. The scenarios are divided into 3 groups: unfavorable, average, and favorable. According to the average scenario, the model forecasts the rise of the discharge up to 180—220 m3/s at the Desna outlet due to the double monthly norm of precipitation in May. For the first time, the summer peak of the hydrograph might overtop the spring one. We are planning to improve the forecast by automating the modeling routine, expanding the set of weather scenarios, and in-depth adjusting the groundwater parameters of the SWAT model.